An updated species list for “Smoky Bears”: Tardigrades of the Great Smoky Mountains National Park, USA - Bartels, Paul J.; Nelson, Diane R.; Kaczmarek, Łukasz (Zootaxa, 2021)
One of the largest inventories of tardigrades ever conducted occurred from 2000–2010 in the Great Smoky Mountains National Park, USA. Over 16,000 specimens were catalogued, 85 species were identified, 11 species new to science were described, and 16 other possible new species await further study. More than 20 papers have resulted from the GSMNP tardigrade inventory, making the Smokies the most thoroughly studied area in North America for tardigrades. Several species lists have been published over this 20-year period, but many taxonomic revisions and new identifications have led to significant changes to the list. Biogeographical studies citing species records from earlier studies could yield serious errors. Here we update the species list from the Smokies to accommodate the many recent changes in tardigrade taxonomy, we re-analyze some species in light of delineations of cryptic species groups that have occurred recently via integrative taxonomy, and we provide a table of all synonyms that have been used in previous publications. We also make available, for the first time, the Smokies tardigrade database, complete with all locations, elevations, and substrates.